Estimation possibilities of damages after earthquakes - Kovács, Előd; Lipovits, Ágnes (Acta Agraria Kaposváriensis, 2006)
In our essay we tried to present some possible approaches of the annual earthquake numbers’ statistical investigation, happening in Hungary. We aimed to demonstrate on an interesting series of data the usefulness of the MCMC method, more and more applied in the last years. We pointed out that the most often applied distributions do not apt well to our data. We approached the frequencies with the mixed Poisson distribution acceptably, but the results, received by the evaluation of the hidden Markov model, suggest that the annual numbers of frequencies are not independent of each other. We developed computer application for collecting data and simulation scenarios of earthquake numbers for the next 20 years. Future events might be easily simulated with the presented program, applying for insurance calculations for example.
Keywords: earthquakes; mixed Poisson distribution; hidden Markov model